The extracellular matrix of lymph node reticular fibers modulates follicle border interactions and germinal center formation - Jian Song; Tushar Deshpande; Xueli Zhang; Melanie-Jane Hannocks; Nils Lycke; Susanna L. Cardell; Lydia Sorokin (iScience, 2023)
Summary: Germinal center (GC) formation and antibody production in lymph node follicles require coordinated interactions between B-cells, T-cells and dendritic cells (DCs), orchestrated by the extracellular matrix-rich reticular fiber (RF) network. We describe a unique laminin 523-containing RF network around and between follicles that associates with PDGFrecβhighCCL19lowgp38low fibroblastic reticular cells (FRC). In the absence of FRC expression of laminin α5 (pdgfrb-cre:Lama5fl/fl), pre-Tfh-cells, B-cells and DCs are displaced from follicle borders, correlating with fewer Tfh-cells and GC B-cells. Total DCs are not altered in pdgfrb-cre:Lama5fl/fl mice, but cDC2s, which localize to laminin α5 in RFs at follicle borders, are reduced. In addition, PDGFrecβhighCCL19lowgp38low FRCs show lower Ch25h expression, required for 7α,25-dihydroxycholesterol synthesis that attracts pre-Tfh-cells, B-cells and DCs to follicle borders. We propose that RF basement membrane components represent a type of tissue memory that guides the localization and differentiation of both specialized FRC and DC populations, required for normal lymph node function.